2020
DOI: 10.1007/s10597-020-00701-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impacts of the COVID-19 Pandemic on the Public in Egypt

Abstract: This study aimed to evaluate the prevalence of depression, anxiety, stress, and inadequate sleeping among the public in Egypt during the novel Corona Virus Disease (COVID-19) pandemic. An online snowball sampling approach was used to collect data from netizens in four Egyptian governorates between 16 and 30 April 2020. A semi-structured questionnaire was designed to assess sociodemographic characteristics, sleeping hours per day, and psychological disturbances (depression, anxiety, and stress) of participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 18 publications
7
79
1
2
Order By: Relevance
“…After reading the remaining 72 articles in June and 94 in August ( n = 166), we included 15 and 28 articles in our study, respectively ( n = 43). ( Ahmed et al, 2020a ; Alkhamees et al, 2020 ; Arafa et al, 2020 ; Ayhan Başer et al, 2020 ; Al Banna et al, 2020 ; Bäuerle et al, 2020 ; Choi et al, 2020 ; Cortés-Álvarez et al, 2020 ; Elhai et al, 2020 ; Fernández et al, 2020 ; Forte et al, 2020 ; Fu et al, 2020 ; Fullana et al, 2020 ; Galindo-Vázquez et al, 2020 ; Gao et al, 2020 ; Horesh et al, 2020 ; Huang and Zhao, 2020 ; Huarcaya-Victoria et al, 2020 ; Hyland et al, 2020 ; Islam et al, 2020 ; Kazmi et al, 2020 ; Lei et al, 2020 ; Liu et al, 2020 ; Moghanibashi-Mansourieh, 2020 ; Newby et al, 2020 ; Orellana and Orellana, 2020 ; Ozamiz-Etxebarria et al, 2020 ; Özdin and Bayrak Özdin, 2020 ; Palgi et al, 2020 ; Papandreou et al, 2020 ; Paulino et al, 2020 ; Pieh et al, 2020 ; Rettie and Daniels, 2020 ; Rodríguez-Rey et al, 2020 ; Shevlin et al, 2020 ; Shi et al, 2020 ; Solomou and Constantinidou, 2020 ; Stanton et al, 2020 ; Verma and Mishra, 2020 ; C. Wang et al, 2020a ; Y. Wang et al, 2020 ; Zhao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After reading the remaining 72 articles in June and 94 in August ( n = 166), we included 15 and 28 articles in our study, respectively ( n = 43). ( Ahmed et al, 2020a ; Alkhamees et al, 2020 ; Arafa et al, 2020 ; Ayhan Başer et al, 2020 ; Al Banna et al, 2020 ; Bäuerle et al, 2020 ; Choi et al, 2020 ; Cortés-Álvarez et al, 2020 ; Elhai et al, 2020 ; Fernández et al, 2020 ; Forte et al, 2020 ; Fu et al, 2020 ; Fullana et al, 2020 ; Galindo-Vázquez et al, 2020 ; Gao et al, 2020 ; Horesh et al, 2020 ; Huang and Zhao, 2020 ; Huarcaya-Victoria et al, 2020 ; Hyland et al, 2020 ; Islam et al, 2020 ; Kazmi et al, 2020 ; Lei et al, 2020 ; Liu et al, 2020 ; Moghanibashi-Mansourieh, 2020 ; Newby et al, 2020 ; Orellana and Orellana, 2020 ; Ozamiz-Etxebarria et al, 2020 ; Özdin and Bayrak Özdin, 2020 ; Palgi et al, 2020 ; Papandreou et al, 2020 ; Paulino et al, 2020 ; Pieh et al, 2020 ; Rettie and Daniels, 2020 ; Rodríguez-Rey et al, 2020 ; Shevlin et al, 2020 ; Shi et al, 2020 ; Solomou and Constantinidou, 2020 ; Stanton et al, 2020 ; Verma and Mishra, 2020 ; C. Wang et al, 2020a ; Y. Wang et al, 2020 ; Zhao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding study location, China was the most frequent country with 13 studies ( Ahmed et al, 2020a ; Choi et al, 2020 ; Elhai et al, 2020 ; Fu et al, 2020 ; Gao et al, 2020 ; Guo et al, 2020 ; Huang and Zhao, 2020 ; Lei et al, 2020 ; Liu et al, 2020 ; Shi et al, 2020 ; C. Wang et al, 2020a ; Y. Wang et al, 2020 ; Zhao et al, 2020 ), followed by 12 European studies ( Bäuerle et al, 2020 ; Forte et al, 2020 ; Fullana et al, 2020 ; Hyland et al, 2020 ; Ozamiz-Etxebarria et al, 2020 ; Papandreou et al, 2020 ; Paulino et al, 2020 ; Pieh et al, 2020 ; Rettie and Daniels, 2020 ; Rodríguez-Rey et al, 2020 ; Shevlin et al, 2020 ; Solomou and Constantinidou, 2020 ), 7 Middle Eastern studies ( Alkhamees et al, 2020 ; Arafa et al, 2020 ; Ayhan Başer et al, 2020 ; Horesh et al, 2020 ; Moghanibashi-Mansourieh, 2020 ; Özdin and Bayrak Özdin, 2020 ; Palgi et al, 2020 ), 4 Central and South American studies( Cortés-Álvarez et al, 2020 ; Fernández et al, 2020 ; Galindo-Vázquez et al, 2020 ; Huarcaya-Victoria et al, 2020 ; Orellana and Orellana, 2020 ), 5 South Asian studies ( Al Banna et al, 2020 ; Islam et al, 2020 ; Kazmi et al, 2020 ; Verma and Mishra, 2020 ) and 2 Australian studies ( Newby et al, 2020 ; Stanton et al, 2020 ). The sample size ranged from 204 to 56,679 participants, and the mean age ranged from 23.54 ± 5 years to 50.5 ± 14.9 years in the twenty-nine studies that did report it.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding Arab's world, there are some studies conducted in order to assess the psychological effect for that pandemic either for general population (Alkhamees et al, 2020;Alsalman et al, 2020;Arafa et al, 2020;Burhamah et al, 2020) and for determined subgroups such as healthcare workers (Badahdah et al, 2020;Corbett et al, 2020) . The researchers used different tools and found that there is a psychological impact of that outbreak, and those studies' ndings revealed the presence of stress, anxiety and depression symptoms even at variable degrees.…”
Section: Introductionmentioning
confidence: 99%